A physical perspective to understand myelin. I. A physical answer to Peter’s quadrant mystery - Liu, Yonghong; Yue, Wenji; Yu, Shoujun; Zhou, Tian; Zhang, Yapeng; Zhu, Ran; Song, Bing; Guo, Tianruo; Liu, Fenglin; Huang, Yubin; Wu, Tianzhun; Wang, Hao (Frontiers in Neuroscience, 2022)
In the development of oligodendrocytes in the central nervous systems, the inner and outer tongue of the myelin sheath tend to be located within the same quadrant, which was named as Peters quadrant mystery. In this study, we conduct in silico investigations to explore the possible mechanisms underlying the Peters quadrant mystery. A biophysically detailed model of oligodendrocytes was used to simulate the effect of the actional potential-induced electric field across the myelin sheath. Our simulation suggests that the paranodal channel connecting the inner and outer tongue forms a low impedance route, inducing two high-current zones at the area around the inner and outer tongue. When the inner tongue and outer tongue are located within the same quadrant, the interaction of these two high-current-zones will induce a maximum amplitude and a polarity reverse of the voltage upon the inner tongue, resulting in the same quadrant phenomenon. This model indicates that the growth of myelin follows a simple principle: an external negative or positive E-field can promote or inhibit the growth of the inner tongue, respectively.